(untitled) (Journal of International Studies, 2020)
It was partly the unresolved conflict in Thailand’s deep south, accentuated since January 2004 that led to the military coup of September 19, 2006 which abruptly ended the premiership of ThaksinShinawatra and his regime. Today the resuscitated democracy followingthe general election of December 2007 is still in a state of turbulence.The underlying reasons for this have not changed much. The connectionbetween the conflict in Thailand’s deep south and the Thailand ’spolitical instability at the centre is too obvious to escape notice. Therehave been many attempts to try to understand Thailand ’s politicaldilemmas. As Thailand’s deep south is culturally Malay, unlike the rest of Thailand, and has a chronic history of rebellion against central rule inBangkok, Malay-Muslim separatism is assumed to be the root cause of the problem. This paper argues that the on-going conflict in Thailand ’sdeep south is actually a function of a complex interplay of factors. Theinterconnected issues of the struggle for cultural autonomy, Thai national security, irredentism, the fear of international terrorism, geopolitics, the dynamics of regional integration, the growing posture of civil society and the pervasive role of the media demonstrate thiscomplexity as well as its international implications.